Anterior Solid Dual‐Rod Instrumentation and Fusion for Flexible Thoracolumbar or Lumbar Spinal Deformities in Adolescent Idiopathic Scoliosis - McKenna C. Noe, BS; Kenneth A. Furlough, MD; Richard M. Schwend, MD (Elsevier, 2024)
Background: Anterior spinal instrumentation and fusion (ASIF) via a thoracolumbar approach has been used to treat Lenke 5 adolescent idiopathic scoliosis for decades. Advances in ASIF technique and instrumentation have yielded significant improvements in rates of instrumentation failure, need for reoperation, instrumented and adjacent segment kyphosis, and pseudarthrosis. Despite reports of ASIF's success using these strategies, a detailed technical description with illustrations of this procedure in the literature is lacking. Methods: We present a detailed illustrated surgical technique guide for anterior solid-rod instrumentation via a thoracoabdominal approach in the correction of a Lenke 5 adolescent idiopathic scoliosis deformity. Results: ASIF through a thoracoabdominal approach allows for excellent coronal and axial correction of the primary structural curve while possibly instrumenting fewer vertebrae and sparing the paraspinal muscles compared to posterior instrumented fusion. This is especially appealing to adolescent athletes who want to preserve spine mobility, as the fusion of fewer spine segments may provide more physiologic functional mobility of the spine. Transiently lowered pulmonary function due to the incision and repair of the diaphragm is expected. Pitfalls to avoid include leaving unrepaired peritoneal holes, improper detachment and repair of the diaphragm, injury to the genitofemoral nerve, violating the spinal canal with screws, fusing too few segments, screw pullout in osteopenic bone, and irritation of the intercostal nerve. Conclusion: We describe the indications for anterior instrumented fusion, preoperative preparation, detailed and illustrated intraoperative technique, and postoperative care. Key concepts: (1) Excellent curve correction. (2) Low rates implant failure, pseudarthrosis, and proximal junctional kyphosis. (3) Benefits-fewer fused segments, less infection risk, preserved posterior muscles. (4) Pitfalls- coronal imbalance, screw pullout, psoas irritation, numbness.